Governance and fight against the poverty - Estévez Araujo, José (2017)
This paper attempts to analyze policies against poverty undertaken by Spain within the framework of the Europe 2020 strategy. These policies have been applied through mechanisms of governance mechanisms -specifically, the so-called democratic experimentalism- whose effectiveness and legitimacy is at least questionable. To this end, this paper tries to analyze, on one side, the European Semester, which coordinates these policies at an EU level. On the other, various Spanish documents that are part of this process and therefore allow us assess the levels of democratic effectiveness of this mechanism.